Provenance Research: Book History, Historiography, and the Rise of an Epistemic Category in Nineteenth‑Century Europe - Hagström Molin, Emma (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2022)
This article considers the rise of provenance in nineteenth-century Europe through a case study of manuscript research. In the early 1850s, Benedictine scholar Beda Dudík was sent to Stockholm and Rome by the Committee of the Moravian Estates in Habsburg Austria to trace manuscript objects abducted from Moravia (Mähren) by Swedish commanders during the Thirty Years’ War (1618–1648). This article considers Dudík’s work with the manuscripts by combining perspectives from book history with those of the history of historiography and the history of ideas and science: I examine the ways in which Dudík worked with classification, and how this work was influenced by source fetishization. Dudík’s work with the manuscripts, recorded in his publications and notes, reveals that provenance is a transformable epistemic category. Moravian interest in provenance reflects their sense of scholarly inferiority, and the changing view of heritage as a public matter, collectively fetishized. In conclusion, the Moravian case illustrates just how significant historical materiality was to people of marginal lands, as inquiries into provenance can be a means of asserting historical existence.